Creating Peru’s patient zero: pandemic narratives through traditional and social media - Alejandra Ruiz-León (História, Ciências, Saúde: Manguinhos, 2023)
Abstract During the covid-19 pandemic, authorities, journalists, and the public used the term patient zero to refer to the first diagnosed patient. However, experts describe the term as imprecise because it equates the first infected patient with the first identified one. Although the term’s inaccuracy, patients zero became relevant actors and sources of information during the pandemic. This was the case with the Peruvian patient zero, who had public media participation and opened his Instagram to establish a communication channel with the public. Despite knowing the term’s inaccuracy, he felt responsible for the audience and sought to give his testimony. The Peruvian case shows how patients zero respond to the public interest and establish their agency through traditional and social media.